2015
DOI: 10.1021/acschembio.5b00268
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Targeting of Doxorubicin Eliminates Nuclear Effects Associated with Cardiotoxicity

Abstract: Abstract:The highly effective anticancer agent doxorubicin (Dox), is a frontline drug used to treat a number of cancers including leukemias, ovarian, prostate, breast, and lung cancer. While Dox has a high level of activity against cancer cells, treatment is often complicated by doselimiting cardiotoxicity. For many years, this debilitating side effect is thought to originate from the drug's direct activity in the mitochondria of cardiac cells, while recent studies have shown that these are primarily downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 40 publications
2
50
0
Order By: Relevance
“…Recently, Jean et al 64 showed that mice treated with a chemically modified doxorubicin derivative, which exclusively enters mitochondria but not the nucleus, lack cardiotoxicity, arguing against a dominant contribution of mtDNA damage in the development of cardiomyopathy following anthracycline treatment. The authors suggest that altered nuclear expression of genes encoding mitochondrial biogenesis factors such as NRF1 and TFAM, is more relevant for the onset of cardiotoxicity than direct mitochondrial damage.…”
Section: Mechanisms Of Anthracycline-induced Cardiotoxicitymentioning
confidence: 99%
“…Recently, Jean et al 64 showed that mice treated with a chemically modified doxorubicin derivative, which exclusively enters mitochondria but not the nucleus, lack cardiotoxicity, arguing against a dominant contribution of mtDNA damage in the development of cardiomyopathy following anthracycline treatment. The authors suggest that altered nuclear expression of genes encoding mitochondrial biogenesis factors such as NRF1 and TFAM, is more relevant for the onset of cardiotoxicity than direct mitochondrial damage.…”
Section: Mechanisms Of Anthracycline-induced Cardiotoxicitymentioning
confidence: 99%
“…Another exciting advantage of mitochondrial targeting for anticancer therapy is the amelioration of off‐target toxicities. When doxorubicin (DOX) was chemically modified into a mitochondrial‐targeted DOX, its cardiotoxicity was decreased, while maintaining its anticancer activity . Additionally, DOX targeted delivery to mitochondria can effectively improve the therapeutic efficacy of DOX in human cancer cell sensitive and resistant cancer .…”
mentioning
confidence: 99%
“…On the other hand, mitochondria-targeting DOX (mtDOX) provided a means to limit drug efflux and inhibited mitochondrial DNA topoisomerase even in the efflux pump overexpressed cells. The same group reported that mtDOX eliminates nuclear effects associated with cardiotoxicity leading to mitochondrial biogenesis [51]. Although DOX has a high level of activity against cancer cells, side effects, such as dose-limiting cardiotoxicity, are a bottleneck for clinical usage.…”
Section: Mitochondria-targeted Peptidesmentioning
confidence: 99%
“…(A) Chemical structure of mitochondria-penetrating peptides (MPPs) conjugated with anticancer drug cisplatin (mtPt), (B) cell cytotoxicity of mtPt in A2780 WT(wild type) and cisplatin-resistant A2780CP70 cell for an incubation time of 72 h showing similar cytotoxicity in both cell lines, (C) chemical structure of MPP conjugated with anticancer drug doxorubicin (mtDox), (D) cell cytotoxicity of mtDox in A2780ADR for a treatment period of 24 h showing higher cytotoxicity of mtDox compared with Dox. (Copyright permission received from reference[51] and[52]). …”
mentioning
confidence: 99%